INFLUENCE STRUCTURE ON THE PLASTICITY OF CARBON STEEL OF THE RAILWAY WHEEL RIM IN OPERATION - Igor Alex VAKULENKO; Leonid VAKULENKO; Dariy BOLOTOVA; Bulent KURT; Hangardash ASGAROV; Ömer ÇÖLOVA (Scientific Journal of Silesian University of Technology. Series Transport, 2022)
When simulating the operating conditions of the rim of a railway wheel, an analysis of change in the structural state from the possible degree of plastic deformation and the heating temperature of steel near the rolling surface was carried out. The development processes of spheroidization and coalescence of cementite during heating of the cold-worked steel change its ability to strain hardening. Substructure changes during heating to temperatures of 500-550°C deformed steel are accompanied by a simultaneous decrease in its ability to strain hardening and the level of plasticity. When heated above 500-550°C, the development of ferrite recrystallization processes provides a gradual transition of the metal from substructure hardening to hardening from grain boundaries with large angles of disorientation. It is shown that regardless of the nature of the main structural element, the ability of steel to strain hardening and the level of plasticity after heating are related by a proportional relationship.